Seawater carbonate chemistry and primary production of Eukaryotic phytoplankton in the tropical and subtropical oceans - Dai, Rongbo; Wen, Zuozhu; Hong, Haizheng; Browning, Thomas J; Hu, Xiaohua; Chen, Ze; Liu, Xin; Dai, Minhan; Morel, Francois M M; Shi, Dalin (PANGAEA, 2025)
Here, we investigate the responses of phytoplankton community composition and productivity to acidification across the western North Pacific. In this six-year study, we conducted 48 onboard microcosm CO2 enrichment experiments (10 to 20 L volume; ~3 d durations) at 45 stations throughout the western North Pacific, spanning the oligotrophic North Pacific Subtropical Gyre and the northern South China Sea to the west, as well as the North Pacific Transition Zone at the northern boundary. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were extracted from tables in the related paper (see Related to) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-05-12. Comment "T" for pH value means these pHT values were converted from electrode-based pH measurements using a calibration relationship established between electrode-based and spectrophotometric measurements within the pH range of 7.4–8.4.
Keywords: Bottles or small containers/Aquaria (<20 L); Coast and continental shelf; Community composition and diversity; Entire community; Laboratory experiment; Macro-nutrients; North Pacific; Open ocean; Pelagos; Primary production/Photosynthesis; Temperate; Tropical